2012
DOI: 10.4028/www.scientific.net/kem.517.622
|View full text |Cite
|
Sign up to set email alerts
|

Activation Alkaline Waste Kaolin for Fabrication of Building Blocks

Abstract: In the state of Paraíba, one of the activities of great economic importance is that of the kaolin processing industry. This type of processing generates large amounts of waste that are displayed randomly in the environment, which has attracted attention, because the environmental impact caused by it and the lack of established process of recycling. The University Federal o Paraíba has been developing several research to explore the potential for recycling of industrial waste from Paraíba, mainly waste of kaoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Universidad Autónoma del Estado de Hidalgo ISSN: 2395-8405 pág. 30 con silicato de sodio e hidróxido de calcio, ha sido empleado por Gómez et al, para la fabricación de block de construcción [13]. Con las arenas de caolín se han logrado producir cerámicos con alta resistencia térmica, gracias a sus propiedades puzolánicas se ha empleado para la elaboración de cementos [14,15].…”
Section: Vol 4 (2017)unclassified
“…Universidad Autónoma del Estado de Hidalgo ISSN: 2395-8405 pág. 30 con silicato de sodio e hidróxido de calcio, ha sido empleado por Gómez et al, para la fabricación de block de construcción [13]. Con las arenas de caolín se han logrado producir cerámicos con alta resistencia térmica, gracias a sus propiedades puzolánicas se ha empleado para la elaboración de cementos [14,15].…”
Section: Vol 4 (2017)unclassified
“…The main geopolymers precursors used are fly ash and blast furnace slag but also metakaolin. However, other materials such as kaolin waste, red brick waste and weathered soils have not been systematically investigated with regard to development of matrices geopolymerics [10][11][12], possibly because such precursors often contain much lower amounts of aluminium and very high amounts of iron oxide when compared to the main precursors. This paper aims to access the potential use of iron rich sources as precursors for alkaline activation.…”
Section: Introductionmentioning
confidence: 99%
“…A previous paper of this project [11], looking at the performance of the waste in AAC mortar, showed that the increase of the water demand was the main reason for the reduction in the compressive strength of the test mortars using mica and china clay sand. Other authors have looked at the kaolin waste from Brazil with a focus on altering the leftover kaolinite to metakaolin to use it as binder [12][13][14]. However, that cannot apply to the waste of the UK china clay production, as it does not contain high amounts of left-over kaolinite as present in the waste from Brazil.…”
Section: Introductionmentioning
confidence: 99%